1990
DOI: 10.1111/j.1365-2222.1990.tb03141.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in‐vivo and in‐vitro response to ragweed immunotherapy in children and adults with ragweed‐induced rhinitis

Abstract: In order to compare results of allergen immunotherapy in paediatric and adult populations, 22 children with a history of ragweed hay fever were matched with an equal number of adults for skin sensitivity to ragweed and all were given a 1-year course of immunotherapy with a partially purified ragweed extract. Biological responses were measured by nasal challenges with ragweed before therapy was started, after 12 weekly injections and when the maintenance dose had been reached and also by methacholine bronchopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…This increase in specific IgE antibodies did however not reflect the clinical improve ment during 6 months of RIT. In agreement with other au thors [25,26], a significant clinical benefit was observed even after 3 months of immunotherapy; early changes in specific IgE concentration do not appear to be the principal mechanism of immunotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This increase in specific IgE antibodies did however not reflect the clinical improve ment during 6 months of RIT. In agreement with other au thors [25,26], a significant clinical benefit was observed even after 3 months of immunotherapy; early changes in specific IgE concentration do not appear to be the principal mechanism of immunotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…However, several possibilities have been proposed, which include altered regulation of IgE synthesis [23], production of blocking antibodies [9], and decreased reactivity of ef fector mechanisms [24], Our finding of a transient increment in specific IgE anti bodies during specific immunotherapy is in accord with the majority o f other studies [7,10,25]. This increase in specific IgE antibodies did however not reflect the clinical improve ment during 6 months of RIT.…”
Section: Discussionsupporting
confidence: 85%
“…Specific immunotherapy (IT) administered by the subcutaneous route has been shown to be effective in the treatment of respiratory allergic disorders [1, 2, 3, 4]. However, subcutaneous IT has been associated with a certain risk of severe or even fatal systemic reactions [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…While Creticos et al (13) found no significant correlations between the effect of immunotherapy on nasal mediator release and specific IgG response, Hedlin et al (1) found a correlation between the decline in TAMEesterase activity and the increase in ragweed IgG and ragweed IgG4 in children. In our study, we could show a significant correlation between the hyposensitization-determined decrease of the TAMEesterase activity and bradykinin concentration and the increase of the specific IgG (P<0.01 and P < 0.05, respectively).…”
Section: -Ementioning
confidence: 97%
“…A direct correlation has not yet been clearly demonstrated between the clinical effectiveness of immunotherapy and IgG antibody production poor reproducibility) part of both the physician and the patient (1)(2)(3). Zn vivo measurement of mediator release in the nasal secretion of allergic patients after nasal allergen challenge now permits an objective evaluation of hyposensitization independently of the subjective parameters mentioned.…”
mentioning
confidence: 99%